Carbon Nanotubes and Nanohorn Hybrid Composite Buckypaper as Microporous Layer for Proton Exchange Membrane Fuel Cell. Issue 3 (1st June 2016) - Ebenezer, D.; Neelima, K.; Jagannatham, M.; Haridoss, P.
Abstract: In the present work, carbon nanotubes (CNT) and CNT‐carbon nanohorns (CNH) (0, 30, 50, 70 and 100 wt.% CNH) composite Buckypapers (BPs) were fabricated using vacuum filtration technique. Structure and property relation of composite BPs were studied using scanning electron microscope, four probe technique, BET surface area and contact angle measurements. Properties such as electrical conductivity, hydrophobic nature and microstructure of CNT‐30 wt.% CNH composite BP are superior to other composite BP. Hence, CNT‐30 wt.% CNH composite BP is chosen as a microporous layer (MPL) for PEMFCs and tested in fuel cell testing fixture. Polarization studies reveal that the cells performance with composite BPs is comparable with SGL‐MPL based cell. Hydrogen pumping and polarization studies of the cells confirms that composite BPs act as a good MPL at anode as well as cathode at 0.4 to 0.8 V. Hence, CNT‐CNH composite BPs are potential candidates for PEMFC applications.